Ontogeny as a method to evaluate classification systems: the case of music in the DDC - Pegoraro Novaes, Fernanda Carolina [UNESP]; Moreira, Walter [UNESP] (Univ Zaragoza, 2020)
Ontogeny is understood as the study of the life span of a specific subject and also as a historical method to research knowledge and its changes over time. Some studies use ontogeny to research classification systems: for example, how their classes and semantics change, among others. In this work, ontogenesis is applied to the music division in the Dewey Decimal Classification (DDC). Several kinds of structural changes were detected: change of synonym in the title and conceptual expansion through subject categories; conceptual expansion of the subject without alteration synonym in the title; adding a new standard subdivision and deleting a standard subdivision for structural changes; adding new words in the title, deleting words in the title and changing the synonym of the title for changes in word usage; and change in the synonym of the title and the set of conceptual description for textual change. This study emphasizes the importance of ontogeny as a method for understanding classification systems, as well as demonstrating, through the identified
Keywords: Dewey Decimal Classification; Ontogeny; Music